Enhancement of creep properties and microstructural stability of intermetallic β-solidifying γ-TiAl based alloys. (August 2015) - Kastenhuber, M.; Rashkova, B.; Clemens, H.; Mayer, S.
Abstract: Carbon, Mo and Si represent promising alloying elements with respect to increase the operating temperature of intermetallic titanium aluminides. The influence of these elements on microstructural stability and creep properties is investigated on a β-solidifying γ-TiAl based alloy, named TNM, with a nominal composition of Ti-43.5Al-4Nb-1Mo-0.1B (in at.%) in two different microstructural conditions. The first condition after casting and hot isostatic pressing has a coarse "nearly lamellar γ" microstructure. The second condition is adjusted by a subsequent heat treatment and shows a "nearly lamellar β" microstructure with finely spaced α2 and γ lamellae and areas of discontinuous precipitation (cellular reaction) in the α2 /γ-colonies. Creep tests were carried out at 815 °C and 150 MPa to examine the influence of microstructure and its change on and during creep. Alloying of C and Si or Mo to the TNM based material led to improved creep properties and microstructural stability by inhibiting the progress of discontinuous precipitation. Highlights: Development of a new β-solidifying multi-phase γ-TiAl based alloy, the so called TNM + alloy. Improving the creep properties and microstructural stability by alloying with C and Si. Studying the solid solution effect of C and Mo as well as precipitation hardening by carbides.